Participatory Research with Teachers - A Critical Analysis of Power Dynamics - Schmidt, Rebecca (Transdisziplinäre Räume in den Kulturwissenschaften)

Aufruhr im Raum der Räume: Logik zwischen Philosophie und Mathematik - Peckhaus, Volker (Transdisziplinäre Räume in den Kulturwissenschaften)

Robust and Efficient Hybrid Optimal Control via Gaussian Process Regression and Multiple Shooting With Experimental Validation on a Double Pendulum on a Cart - Hesse, Michael; Schwarzer, Luis; Timmermann, Julia; Trächtler, Ansgar (PAMM)
ABSTRACT In this contribution, we propose an innovative method for determining optimal control sequences for nonlinear systems with partially unknown dynamics, which further expands our previous work. Within the paradigm of model‐based design, the practicality and safety of commissioning feedforward controls and feedback controllers have priority. Our approach leverages probabilistic Gaussian processes to adjust for model inaccuracies from measured system data. This differs from conventional approaches that involve complicated analytical modeling and may entail a substantial time investment to acquire expertise and may prove impractical. Consequently, we address the limitations inherent in traditional design methodologies. Our research focuses on the formulation and solution of the hybrid 1 optimal control problem using probabilistic state predictions and multiple shooting. This ensures adaptability, data efficiency, and resilience against uncertainties in system dynamics. These attributes are empirically substantiated through experimental validation on a chaotic and highly sensitive dynamical system—a double pendulum on a cart. Our methodology unfolds as an iterative learning process, systematically exploring diverse controls, accumulating data within each iteration, and refining the control strategy until the desired task is accomplished. The adoption of the two‐degree‐of‐freedom control structure allows for the distinct consideration of the feedforward and the feedback control signal. For the latter, we employ a time‐variant, linear quadratic regulator (LQR) designed to stabilize the system around its target trajectory. Furthermore, we integrate a probabilistic long‐term prediction through the unscented transform, enabling systematic anticipation of safety‐critical violations. Detailed insights into relevant implementation aspects are provided. To ascertain the real‐world applicability, we present an exemplary application involving a double pendulum on a cart. The objective is to bring the pendulum arms from the lower stable to the upper unstable equilibrium by horizontally moving the cart and subsequently stabilize them. In this scenario, we assume that the centrifugal forces, crucial to the system dynamics, have not been accurately modeled and must be learned from data. Solving the control task took only 5 iterations and 1 h of computation time, which surpasses our previous work [2], where we used the purely data‐driven PILCO framework and required 27 iterations and 57 h of computation time. The time of interaction with the system decreased by and the computation time is lowered by . It demonstrates significant practical applicability for commissioning control systems.

ANTS: Abstractive Entity Summarization in Knowledge Graphs - Firmansyah, Asep Fajar; Zahera, Hamada Mohamed Abdelsamee; Sherif, Mohamed; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (ESWC2025)
Keywords: firmansyah mousallem ngonga sherif zahera

GLIDE: Knowledge Graph Linking using Distance-Aware Embeddings - Becker, Alexander; Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed (The Semantic Web – ISWC 2025)
The number of datasets on the web of data increases continuously. However, the knowledge contained therein cannot be fully utilized without finding links between the entities contained in these datasets. Equivalent entities can not be identified solely by checking the equivalence of IRIs because of the different origins and naming schemes of different data providers. Yet, such equivalences can be discovered by computing the similarity of their attributes. In this paper we propose GLIDE, an approach that links entities from two different datasets by embedding a joint model of these datasets enriched by additional relations describing the similarity of literals. The joint model is embedded into a latent vector space while paying attention to juxtaposing similar literals. We evaluate our approach against state-of-the-art algorithms using real-world datasets commonly used in link discovery literature. The results show that GLIDE outperforms all baselines on 5 of 7 datasets with perfect or near-perfect accuracy. Our approach achieves its best performance on datasets that feature several literals with similarities. Our experiments indicate that researchers should not only pay attention to equal literals in knowledge graph embedding but should also be aware of the distance between similar literals.
Keywords: becker sherif enexa sailproject dice simba ngonga whale

Metaphors in 24 WIRED Level 5 Videos (Data corpus) - Scharlau, Ingrid; Miriam, Körber

Demonstration of domain wall current in MgO-doped lithium niobate single crystals up to 400°C - Wulfmeier, Hendrik; Yakhnevych, Uliana; Boekhoff, Cornelius; Diima, Allan; Kunzner, Marlo; Verhoff, Leonard M.; Paul, Jonas; Ratzenberger, Julius; Beyreuther, Elke; Gössel, Joshua; Kiseleva, Iuliia; Rüsing, Michael; et al. (Solid State Ionics)
Conductive ferroelectric domain walls (DWs) represent a promising topical system for the development of nanoelectronic components and device sensors to be operational at elevated temperatures. DWs show very different properties as compared to their hosting bulk crystal, in particular with respect to the high local electrical conductivity. The objective of this work is to demonstrate DW conductivity up to temperatures as high as 400 °C which extends previous studies significantly. Experimental investigation of the DW conductivity of charged, inclined DWs is performed using 5 mol % MgO-doped lithium niobate single crystals. Current–voltage ( ) curves are determined by DC electrometer measurements and impedance spectroscopy and found to be identical. Moreover, impedance spectroscopy enables to recognize artifacts such as damaged electrodes. Temperature dependent measurements over repeated heating cycles reveal two distinct thermal activation energies for a given DW, with the higher of the activation energies only measured at higher temperatures. Depending on the specific sample, the higher activation energy is found above 160 °C to 230 °C. This suggests, in turn, that more than one type of defect/polaron is involved, and that the dominant transport mechanism changes with increasing temperature. First principles atomistic modeling suggests that the conductivity of inclined domain walls cannot be solely explained by the formation of a 2D carrier gas and must be supported by hopping processes. This holds true even at temperatures as high as 400 °C. Our investigations underline the potential to extend DW current based nanoelectronic and sensor applications even into the so-far unexplored temperature range up to 400 °C.

KI-gestützter Umgang mit Textprodukten im prozessorientierten DaF-Unterricht. - Ballweg, Sandra (Erträge des JGG-Seminars für Deutsch als Fremdsprache Leistungsbeurteilung und Schreibprodukte)

"man hat sich halt online getroffen". Zur Aushandlung räumlicher Praktiken in virtuellen Austauschbegegnungen. - Ballweg, Sandra (Fremdsprachenlehren und -lernen zim Spannungsfeld von digital und analog)

Das Gesicht des Weltalls anschauen. Rilkes Ägypten-Reise und der Kulturtourismus - Schulte Eickholt, Swen (diMaG)
Als Rilke im Frühjahr 1911 eine zuvor begonnene Afrika-Reise mit einem Nildampfer von Thomas Cook in Ägypten fortsetzt, wird ihm schnell klar, dass das Tempo des Massentourismus in Konflikt mit seinen Sehbedürfnissen kommt. Der touristische Blick entsteht in zeitlicher und gedanklicher Nähe zum Kolonialismus und führt eine Form eurozentrisch-hegemonialer Weltbeherrschung vor ‒ wobei der Tourist als Typus auch im Inland schon im 19. Jahrhundert dem Reisenden als Negativfigur entgegengestellt wird. Entgegen gegenwärtiger Werbestrategien ist auch der Kulturtourismus von seinen Anfängen her nicht frei von Elementen des Massentourismus und eines die Fremde beherrschenden Blicks. Dass eine immer schon vorgeprägte Erwartungshaltung die erwartete Erschütterung erschwert, wird Rilke auf seiner Reise deutlich, die er nicht zuletzt durch die Ägypten-Reise seiner Frau vorbereitet hat. So versucht er den Ambivalenzen des industrialisierten Kulturtourismus zu entkommen und empfindet am Ende doch nur die strukturelle Untragbarkeit der touristischen Situation, die schon vor der Reise durch die Hoffnung auf authentisches Erleben hoffnungslos kontaminiert ist.

Manners Matter: Action history guides attention and repair choices during interaction - Singh, Amit; Rohlfing, Katharina J. (IEEE International Conference on Development and Learning (ICDL))
This study investigated how action histories – unfolding sequences of actions with objects – provide a context for both attentional allocation and linguistic repair strategies. Building on theories of enactive cognition and sensorimotor contingency theory, we experimentally manipulated action sequences (action history) to create either simple or rich “situational models,” and investigated how these models interact with attention and reflect in linguistic processes during human–robot interaction. Participants (N = 30) engaged in a controlled object placement task with a humanoid robot, where the action (manner) information was either provided or omitted. The omission elicited repair behaviors in participants that were in focus of our investigation. For rich models (competing action possibilities) participants demonstrated: a) increased attentional reorientation, reflecting active engagement with the situational model b) preference for restricted repairs, targeting the specific source of trouble in action selection. Conversely, a simple situational model led to more generalized attention patterns and open repair strategies, suggesting weaker constraints on internal processing. These findings highlight how situational structures emerge externally to scaffold internal cognitive processes, with action histories serving as a crucial context for the interface between perception, action, and language. We discuss how to implement such a tight loop in the assistance of a system.
Keywords: Attention; Action; Repairs; Task model; HRI; Eyemovement

Embedding Psycholinguistics: An Interactive Framework for Studying Language in Action - Singh, Amit; Rohlfing, Katharina J. (6th Biannual Conference of the German Society for Cognitive Science, Bochum, Germany)
We introduce a method to study online language processes in human--robot interactive setup. In this interaction, language mediated eye movements can be studied as the dialogue unfolds between human and a robot. Traditionally, real-time linguistic processes are studied using visual world paradigms (VWP), where either the comprehension or the production tasks are implemented on screens for controlled investigations. Going beyond these traditional and unidirectional approach, we bring together production--comprehension loop with the help of a humanoid robot to preserve interactivity in an ecologically valid yet controlled setup. We discuss the potential of such setups for designing and evaluating findings from language--vision interplay in psycholinguistics. Our setup shows a potential to depart from traditional screen based experiments, balancing the dynamics of the interaction with control of the human behaviors.

'(-)bio(-)' als Bestandteil von Lebensmittelmarkennamen: Eine kognitiv-grammatische Untersuchung zur Komposition von Markennamen - Dübbert, Alexander (Zeitschrift für Wortbildung)
'bioZENTRALE', 'Bio Liebe', 'dmBio', 'Kölln Bio' etc.: Bei der Benamung von Lebensmittelmarken wird die Komponente '(-)bio(-)' angesichts der Verbreitung biologisch hergestellter Produkte häufig eingesetzt. Marken verwenden sie mal in Präposition und mal in Postposition, mal gebunden und mal frei. Dieser Beitrag untersucht diese unterschiedlichen Verwendungen aus einer kognitiv-grammatischen Perspektive anhand eines Korpus aus aktuellen Lebensmittelmarkennamen. Ziel ist es, die Arten der Komposition zu systematisieren. Als Ausgangspunkt dienen die in der linguistischen Forschung bisher üblichen Klassifizierungen von 'bio-' als initiales Konfix sowie 'bio' als Kürzung. Die Analyse zeigt, dass die Komponente '(-)bio(-)' überwiegend als gebundene oder ungebundene spezifizierende Erst- oder auch Zweiteinheit in regulären Konfix-Komposita und kompositumähnlichen Bildungen, die als Markennamen eingesetzt werden, gebraucht wird. Seltener fungiert die Komponente selbst als Profildeterminante. Die Komponente '(-)bio(-)' wird demzufolge zur Bildung von Markennamen variabler gebraucht, als durch die Einordnung von bio- als vornehmlich linke, gebundene Einheit in Komposita bislang angenommen wurde.
Keywords: Markennamen; Konfix; bio; Kognitive Grammatik

WATS up? What About Teacher Shortage? International Perspectives from Denmark, Germany, and Sweden - Boström, Lena; Kreienbaum, Maria Anna; Wüllner, Sabrina; Ørsted Andersen, Frans; Bostedt, Göran; Håkansson Lindqvist, Marcia (Teacher Shortage in International Perspectives: Insights and Responses. Non-Traditional Pathways to the Teacher Profession)

Teacher Shortages in Germany – Causes, Countermeasures, and Assessments by Educational Scientists - Kreienbaum, Maria Anna; Wüllner, Sabrina (Teacher Shortage in International Perspectives: Insights and Responses. Non-Traditional Pathways to the Teacher Profession)

Künstliche Intelligenz in der Kriegsführung. Überblick, Hoffnungen und Risiken - Hälterlein, Jens (Marxistische Blätter)

Autonome Waffensysteme und Meaningful Human Control - Hälterlein, Jens (Marxistische Blätter)

‚Novellierungen‘ der Novellistik. Der ‚Fall‘ der Novelas ejemplares - Schlieper, Hendrik (Artes)

Mercedes. Gunst und Affekt in Cervantes’ La española inglesa - Schlieper, Hendrik (Artes)

Geschichte und Umwelt von Rechenzentren; Rezension zu: Dommann, Monika; Rickli, Hannes; Stadler, Max (Hrsg.): Data Centers. Edges of a Wired Nation, Zürich 2020; Gugerli, David; Wichum, Ricky: An den Grenzen der Berechenbarkeit. Supercomputing in Stuttgart, Zürich 2021 - Schmitt, Martin (HSozKult)
Keywords: Rechenzentren; Geschichte; Umweltgeschichte; Nachhaltigkeit; Supercomputing; Technikgeschichte